Sketching and context: Exploring creativity in idea generation groups. (January 2023) - Paay, Jeni; Kjeldskov, Jesper; Bønnerup, Michael; Rasenthiran, Thulasika
Abstract: Studies of creativity have shown that idea generation within groups produces fewer novel ideas. To address this, we examine ways to stimulate the creative process in idea generation groups, and contribute the new technique of "brainsketching with context cues", which purposefully adds contextual input into the sketching activity. We build on the existing brainsketching technique, which promotes idea sharing during sketching, by adding context cards into the process. To investigate if sketching with contextual input supports creativity in the design process, we analysed six design sessions with 15 young Interaction Designers. Our findings show that contextual input enhances both individual and group creativity by supporting idea and information exchange in the sketching activity, increasing diversity and novelty of design outcomes. Highlights: Using context cues in brainsketching to stimulate idea generation in groups. Using linkography to analyse ideation sessions and trace links between ideas. Context cues enhance both individual and group creativity. Abstract context cues stimulate the group to generate ideas that are more novel and creative.